2020
DOI: 10.2478/acph-2021-0003
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of olive oil phenolics oleuropein and hydroxytyrosol against hydrogen peroxide-induced DNA damage in human peripheral lymphocytes

Abstract: This study investigates antioxidant capacity and protective effects of phenolic compounds oleuropein (OLP) and hydroxytyrosol (HT), present in olive oil and olive leaves, against H2O2-induced DNA damage in human peripheral lymphocytes. Antioxidant potency was determined using the measurement of radical-scavenging activity (ABTS∙+ assay), ferric reducing power (FRAP assay) and cupric reducing antioxidant capacity (CUPRAC assay). Both substances were found to be potent antioxidant agents due to their free radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Recent studies highlighted the anti-genotoxicity in liver tissue of the major metabolites in AE-EOP and AAE-EOP extracts, such as mannitol 48 and hydroxytyrosol. 49 The present findings also revealed that CCl 4 induced perturbation of the lipid profile as observed by considerably increased levels either in plasma and hepatic tissue of TC, TG and LDL-C, while HDL-C levels decreased. These changes in lipids parameters have been observed after CCl 4 administration.…”
Section: Papersupporting
confidence: 73%
See 1 more Smart Citation
“…Recent studies highlighted the anti-genotoxicity in liver tissue of the major metabolites in AE-EOP and AAE-EOP extracts, such as mannitol 48 and hydroxytyrosol. 49 The present findings also revealed that CCl 4 induced perturbation of the lipid profile as observed by considerably increased levels either in plasma and hepatic tissue of TC, TG and LDL-C, while HDL-C levels decreased. These changes in lipids parameters have been observed after CCl 4 administration.…”
Section: Papersupporting
confidence: 73%
“…Recent studies highlighted the anti-genotoxicity in liver tissue of the major metabolites in AE-EOP and AAE-EOP extracts, such as mannitol 48 and hydroxytyrosol. 49…”
Section: Discussionmentioning
confidence: 99%
“…Further studies focusing on the bio-accessibility of polyphenols after enzymatic digestion of different Olea europaea products have been extensively reviewed elsewhere [ 120 ]. Oleuropein and hydroxytyrosol antioxidant activity seemed to be similar in an ex vivo study in humans [ 121 ], while both seemed to be more potent than homovanillic alcohol in vitro [ 122 ]. Hydroxytyrosol plasma concentrations diminish within approximately 1 h after EVOO ingestion, as they are transformed into glucuronidated forms, which have similar antioxidant potency to tyrosol [ 123 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ABTS radical scavenging activity was measured using the method described by Kosalec et al (Zoric et al, 2021). ABTS radical scavenging activity was expressed in terms of micrograms of Trolox equivalents per gram of FW basis (μg/g).…”
Section: Antioxidant Capacity Measurementmentioning
confidence: 99%